Visual Design and Digital Storytelling Innovation in Strengthening Brand Identity and Product Appeal for Local Culinary Businesses - Indah Wulandari; Arieviana Ayu Laksmi; Nova Kristiana; Nanda Nini Anggalih; Bayu Nurwicaksono; Riyan Febriansyah; Dzikry Fakhrullah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study examines the challenges of competition and digital adaptation faced by local Micro, Small, and Medium Enterprises (MSMEs) in the digital era, focusing on Salad Taza, a culinary MSME in Kediri City. MSMEs play a vital role in the Indonesian economy but often encounter obstacles in marketing, branding, and technological adaptation, especially in the digital realm. The objective of this research is to design and implement a rebranding strategy and digital promotional media through creative content to enhance the competitiveness of Salad Taza MSME. The Participatory Action Research (PAR) method was employed, involving active collaboration with the partner through stages of problem identification, intervention design and implementation (including visual design and digital storytelling training), continuous observation, and participatory reflection and evaluation. The activity results indicate that brand identity updates and optimization of digital content (photos/videos, storytelling) using simple applications (Canva, CapCut) significantly improved Salad Taza's brand awareness and independent promotional capabilities. Social media optimization with a content calendar and relevant keyword usage also contributed to enhanced marketing effectiveness. The implementation of this strategy not only has the potential to increase sales conversion and customer loyalty but also strengthens the MSME's position in a competitive market, demonstrating an effective university-based MSME empowerment model.